FINANCIAL LITERACY EDUCATION FOR PRESCHOOL STUDENT - Aprita, Yessica Mega; Nuraeni, Yuni Siti; Irawati, Dwi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Financial literacy has been implemented at various levels of education, however, early childhood financial literacy skills have not been fully identified. The purpose of this research was to learn why and how the teachers of the KB 2 Class at Nyai Ahmad Dahlan Full Day School Yogyakarta introduce financial literacy education to their students. This research was classified as qualitative research with a single case research approach. The data was collected through interviews and direct observation by researcher, then analyzed by data collection, data reduction, data presentation, and conclusion drawing. According to the fin3dings of the research, financial literacy education in KB 2 Class was carried out along with the teachers' concerns about Indonesia's high rate of corruption. The education was done by introducing children to various financial concepts and inviting them to practice these concepts based on predetermined indicators. The results showed that 80% of children could distinguish banknotes and coins based on their shape, 100% of students saved at the school bank, 93% of students saved at home with a piggy bank, 93% of students enthusiastically participated in role-playing activities as sellers and buyers, 87% of students participated in market day activities, 67% of students wanted to share with their friends, 80% put money in the infaq box, and 53% could tell their belongings from those of their friends. Keywords: Education, Literacy, Financial Literacy, Preschool, Early Childhood